Validade dos critérios GLIM para diagnóstico de desnutrição em pacientes com câncer colorretal: estudo multicêntrico acerca do desempenho diagnóstico de diferentes indicadores de massa muscular reduzida e de inflamação. - Ana Luiza Soares dos Santos (2022)
Introduction and objectives: The performance of different methods to evaluate reduced muscle mass (MM) and the impact of the disease on diagnosis of malnutrition using GLIM are scarce. The aim of this research was to assess the concurrent and predictive validity of different combinations of GLIM to diagnose malnutrition in patients with colorectal cancer (CRC) considering different alternatives to evaluate reduced MM and impact of the disease. Methods: This was a multicenter cohort study with retrospective analysis of data from patients with CRC. The phenotypic criterion called reduced MM was assessed by anthropometry, bioimpedance and computed tomography. Cancer diagnosis or disease staging (TNM) was considered as the etiologic criterion referred to as impact of the disease. Agreement, sensitivity and specificity between GLIM and nutritional status (PG-SGA) were evaluated. Logistic regression and Cox regression were used in the predictive validation. Results: For concurrent validity (n=208), most GLIM combinations (54.5%) presented moderate agreement with PG-SGA and none of them showed satisfactory sensitivity and specificity (>80%). The combination that presented the best performance was GLIM 5 (BMI or WL or FFMI + RFI or cancer) with sensitivity of 77.3% and specificity of 75.3%. Most combinations were associated with pre-op complications and mortality for the predictive validity (n=121). Reduced MM, SMI and SMI plus SMD stood out for postoperative complications, independently of the etiologic criterion. The presence of reduced MM, considering any method, and TNM were associated with mortality. Conclusion: Satisfactory concurrent validity was not verified. The GLIM diagnosis of malnutrition was associated with postoperative complications and mortality